Is there any impact of the world uncertainty spillover index (wusi) on firm investment? Evidence from Turkey - TAN, ÖMER FARUK (My University, 2023)
This paper examines the impact of the World Uncertainty Spillover Index-United States (WUSI-USA) on the corporate investment policy of 164 Turkish manufacturing firms between 2005 and 2019. According to the findings, the WUSI-USA has a negative impact on the investment policy of firms. Based on the real options theory, firms prefer to postpone their investments under uncertain conditions. The use of alternative measurements of investment confirms the validity of our results. Overall, this study reveals that uncertainty coming from the US affects the investment decisions of firms in Turkey. Therefore, Turkish firms should include uncertainty spillovers in their financial decisions and adjust their strategies based on firm-specific factors in times of uncertainty spillovers. Furthermore, policymakers and firm managers should consider the US uncertainty spillover effects while generating their investment strategies.

Bu makale, Dünya Belirsizlik Yayılma Endeksi-Amerika Birleşik Devletleri'nin (WUSI-USA) 164 Türk imalat firmasının 2005 ve 2019 yılları arasındaki yatırım politikası üzerindeki etkisini incelemektedir. Bulgulara göre, WUSI-USA'nin firmaların yatırım politikası üzerinde olumsuz bir etkisi vardır. Reel opsiyon teorisine göre firmalar belirsiz koşullar altında yatırımlarını ertelemeyi tercih etmektedirler. Alternatif yatırım ölçümlerinin kullanılması, sonuçlarımızın geçerliliğini doğrulamaktadır. Genel olarak, bu çalışma ABD'den gelen belirsizliğin firmaların yatırım kararlarını etkilediğini ortaya koymaktadır. Türk firmaları finansal kararlarına belirsizlik yayılmalarını dahil etmeli ve stratejilerini belirsizliğin yayıldığı zamanlarda firmaya özgü faktörlere göre ayarlamalıdır. Politika yapıcılar ve firma yöneticileri, yatırım stratejilerini oluştururken ABD'deki belirsizlik yayılma etkilerini dikkate almalıdır.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Finansman; Social Sciences and Humanities; Management; Finance; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; Pazarlama; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Marketing; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities; Uncertainty spillovers; firm performance; corporate investment; Turkey; Belirsizlik yayılmaları; firma performansı; kurumsal yatırım; Türkiye